Effect of co-administration of lactobacilli S-layer proteins on immune response against S-layer proteins from pathogenic Clostridioides difficile - Assandri, Matías Hernán (2025)
Introduction. Vaccine adjuvants are essential for enhancing and directing specific immune responses. S-layer proteins (SLPs),which coat the surface of many prokaryotes, can induce a variety of responses, including pro- and anti-inflammatory effects.We have previously shown that the SLP from Lentilactobacillus kefiri CIDCA 8348 enhances antigen-specific cellular responses.Hypothesis. The immunostimulatory activity of SLPs from L. kefiri strains could enhance the specific immune response againstthe SLP from the pathogen Clostridioides difficile, which is emerging as an interesting target for vaccine development.Aim. The aim of this study was to evaluate the effect of SLPs from non-pathogenic L. kefiri strains (SLP-Lk) on the immuneresponse against SLPs from pathogenic C. difficile strains (SLP-Cd), using in vitro and in vivo experiments.Methodology. We evaluated the immunostimulatory ability of both SLP-Lk and SLP-Cd, either alone or in combination, on RAW264.7 macrophages by measurement of secreted IL-6 after 24h of stimulation or by determination of cytokine mRNA expression after 4h of incubation with stimuli. Regarding the results, we assessed the impact of SLP-Lk on the levels of anti-SLP-Cdspecific IgG in mouse sera.Results. Among the five SLP-Lk evaluated, only SLP-Lk 8343 and SLP-Lk 83111 increased IL-6 secretion by RAW 264.7 cells,showing a dose–response behaviour, with no stimulation at 2.5µgml−1. In contrast, neither SLP-Cd 117 nor SLP-Cd 43255induced IL-6 secretion by macrophages at 30µgml−1. However, when RAW 264.7 cells were incubated with a mixture of SLP-Lk8343 or SLP-Lk 83111 (at 2.5µg ml−1) and SLP-Cd 117 or SLP-Cd 43255 (at 30µg ml−1), IL-6 secretion increased significantly,irrespective of the SLP-Lk/SLP-Cd pair analysed. Finally, we found that the intraperitoneal co-administration of SLP-Lk 83111resulted in a significant increase in serum levels of anti-SLP-Cd 43255-specific IgG in immunized mice.Conclusion. The ability of SLP-Lk 83111 to enhance the activation of antigen-presenting cells induced by SLP-Cd 43255 correlates with a significant increase in specific antibodies in the sera of mice immunized with SLP-Cd 43255. Further research isrequired to elucidate the roles of these anti-SLP-Cd antibodies in the context of C. difficile infection.